Determining the spatial variation of phosphorus in a lake system using remote sensing techniques. Issue 1 (March 2014) - Albert Moses, Sheela; Janaki, Letha; Joseph, Sabu; Kizhur Kandathil, Ramachandran
Abstract Lakes are versatile ecosystems, with eutrophication being a serious problem affecting their condition and trophic status. Eutrophication can lead to an over‐abundance of macrophytes in lakes, producing favourable conditions for mosquito larvae. Increased eutrophication is attributed in most to excessive phosphorus concentrations in lake water. Satellite imagery analysis now plays a prominent role for quickly assessing water quality over a large area. The present study is an attempt to illustrate the variation of phosphate and total phosphorus concentrations in Akkulam–Veli Lake, Kerala, India, using Indian Remote Sensing satellite (IRS P6‐ LISS III) imagery. A multiple regression equation derived using radiance in the red and MIR bands in the imagery was found to yield superior results for predicting the phosphate concentration, whereas a simple regression equation using radiance in red band was found to yield good results for the total phosphorus concentration in lake water. Accordingly, the trophic status of the lake system can be determined easily from satellite imagery in this manner.